Male and Female Broilers Response to Different Ideal Amino Acid Ratios During the Second and Third Weeks Posthatch - Taherkhani, R.; Shivazad, M.; Zaghari, M.; Shahneh, A. Zare (International Journal of Poultry Science, 2005)
A chick bioassay with chemically defined amino acid (AA) diets was conducted to compare four different AA profiles: the NRC (1994), Feedstuff, Rhone Poulenc Animal Nutrition (RPAN) and Illinois Ideal Chick Protein (IICP) AA profiles. The ideal ratios of IICP, RPAN and Feedstuff calculated using digestible AA requirements and total AA requirements used for NRC. This battery study involved male and female chicks during 7 to 21 days of age. Indispensable AA were rationed to lysine according to requirement ratios presented in the four profiles. Digestible lysine set at 1.07 and 0.98 % of diet for male and female, respectively. All diets were kept isonitrogenous (2.6 % N) by varying levels of L-glutamic acid. All diets were checked to have at least 0.3 % proline and 0.6 % glycine. Diets for all profiles contained 3200 kcal ME/kg and a positive control diet was used according to NRC (1994) recommendations. Chicks fed a common corn-soybean meal diet for 160 h and were raised in the floor pen. Then chicks weighed individually and allocated to battery pens so that most uniformity among pens occurs. Four battery pens of five chicks were fed one of four different profiles or positive control diet in both sexes. Weight gain and feed intake were measured for each pen at day 21 and then feed:gain was calculated. Results indicate that chicks fed positive control diet weighed more (p< 0.5). Among semi purified diets chicks fed diets formulated with NRC (1994) ideal AA ratios had significantly (P< 0.5) better weight gain and feed:gain in both sexes relative to IICP and RPAN, but not to Feedstuff .RPAN had worst weight gain and feed:gain in females . Results of this experiment suggest that new ideal ratio of threonine (relative to lysine) in IICP for starter period may be under-estimated.